Gemar Makan Ikan untuk Kecerdasan Anak Sekolah di MTS Al-Maidar Pandan Kabupaten Tapanuli Tengah - Emma Suri Yanti Siregar; Tengku Muhammad Ghazali; Rosmasita Rosmasita; Dian Fitria; Juliana Pebrina Siburian; Insaniah Rahimah; Sonia Ginatha; Ahriansah Rao; Esi Wahyuni; Sahraini Sahraini (University of Merdeka Malang, 2021)
Indonesia is a maritime country that has many marine natural resources. Central Tapanuli Regency has a position close to the sea. Even though fish has a high protein content with amino acids, students or young people still like to eat fish a little. So it is necessary to provide information and at the same time invite the younger generation to like to eat fish to increase their intelligence. This community service activity was carried out at MTS Al-Maidar Pandan, Pandan District, Central Tapanuli Regency. The method of implementing this service activity is done by providing socialization about the importance of eating fish for MTS Al Maidar students. The outcomes achieved are increasing students' knowledge about the benefits of fish consumption and the nutritional value contained in fish as well as providing students' understanding with the knowledge to be able to distinguish between fish that are suitable for daily consumption or not.